Tools to develop dairy ingredients: bioactive and preservative purposes - Khouja, Dora (2021)
Phytosterols can be ingested and consequently absorbed by the human body, leading to a direct absorption competition with cholesterol, thus reducing its absorption [1]. Mushrooms are described as having several bioactive components, such as mycosterols (ergosterol), which, similarly to phytosterols, exhibit a strong hypocholesterolemic potential [2]. Thus, the objective of this work was to obtain mycosterol enriched extracts from A. bisporus L. bio-waste for further incorporation in sheep cottage cheese, in order to develop a functional food with hypocholesterolemic effects. Sheep cottage cheeses with pure ergosterol, and a control cheese with no incorporation were prepared. The extracts were obtained by ultrasound assisted extraction (UAE) and the identification and quantification of their compounds was achieved through HPLC-UV. The toxicity and hypocholesterolemic activity were sought through a CaCo2 cell line. In terms of analysis, the nutritional value was analyzed according to AOAC procedures, the physical parameters included texture, external colour and water activity, and the microbial load (total aerobic mesophiles, enterobacteria, Psychrotrophic bacteria, yeasts, molds and Staphylococcus aureus) was also analyzed along a shelf life of 9 days according to the International Organization for Standardization (ISO) 6887-1:2003 [3,4]. No significant differences were verified for the nutritional parameters. The color of the cheeses incorporated with the extract hinted towards a browner tone when compared to the other two samples (cottage cheese with ergosterol and control cottage cheese). A dominance of palmitic acid followed by oleic and capric acids was detected, being the saturated fatty acids the predominant ones. Lactose and glucose were the two detected soluble sugars; being glucose only observed in cheese incorporated with A. bisporus, probably present in the extract. Also, the incorporations did not cause any significant alterations to normal microbial growth. Despite an increase of enterobacteria in the cheeses with the incorporation of the two agents, this increase was also verified for the control cottage cheese. CaCo2 cells absorbed 43.89% of cholesterol from the control cheese, while the cheese with pure ergosterol reduced cholesterol absorption by approximately 21.1%, and cheese with A. bisporus by approximately 30.24%. These results highlight the capacity of ergosterol to reduce the absorption of cholesterol, being an interesting candidate for the development of functional foods.